Construction of Authenticity in Islamic Law: An Analysis of Polygamy, Divorce, and Political Participation of Women - Cheema, Shahbaz Ahmad (Islamic Studies, 2020)
Construction of authenticity in Islamic law on contentious issues including gender-related issues is an outcome of an intricate and complex process of interaction between the divine and human agency situated in a specific sociopolitical context. The divine text is not monolithic and is susceptible of various interpretations. It is this interpretative space, which is employed by scholars coming from various backgrounds to articulate their authenticities. Hence, we do not find one authentic perspective on any issue. Without preferring one perspective to others, the paper aims to analyze the process of constructive mechanics by engaging with the issues of polygamy, dissolution of marriage by divorce and khul‘, and women’s participation in the political domain. For this purpose, it has attempted to deconstruct the constructive process of authenticities relating to these issues with an object to discern how mush these authenticities are the product of the divine agency and where they are influenced by a human agency located in a specific context.